ECOLOGICAL AND BIOLOGICAL CHARACTERISTICS AND PHYTOCENOTIC STRUCTURE OF RHODIOLA QUADRIFIDA POPULATIONS IN EAST KAZAKHSTAN (Experimental biology, 2021)
This study is about investigating the biological characteristics and ecological-phytocenotic confinement of Rhodiola quadrifida in East Kazakhstan. The research was implemented on three mountain ranges: Ivanovsky, Lineisky, and Koksinsky of Kazakhstan Altai. Cenopopulations were studied by using standard geobotanical methods. The species habitats are confined to the alpine and mountain-tundra belt, in the altitude limit of 1800–2400 m asl. Rh. quadrifida mainly grows on outliers, rocks, along fine, coarse talus, moss-lichen, dryad, stony-sedge tundra. High vegetative reproduction is noted in thick moss cover areas. The state of Rh. quadrifida of CP3, CP4, and CP5 is normal and capable of self-sustaining by seed and vegetative manner. CP1 and CP2 species are maintained due to ineffective vegetative reproduction. Rh. quadrifida is an extremely rare species that is rapidly reducing the number and area of populations, it is necessary to be included in the next edition of the Red Book of Kazakhstan.